Nursing of a patient with early-stage acute mastitis of Qi-stagnation and heat-obstruction type treated by Bian-stone therapy (砭石技术治疗1例乳痈初起气滞热壅型患者的护理体会) - LIU Shanshan (刘姗姗); CHEN Hong (陈宏); ZHEN Ruiwen (郑睿文); XU Jingjin (徐京巾); ZHANG Jing (张敬); TANG Ling (唐玲) (Association of Integrative Nursing, 2022)
This paper reported the therapeutic effect of Bian-stone therapy for a patient with with early-stage acute mastitis of Qi-stagnation and heat-obstruction type, and summarized the technical principle and operation process of Bian-stone therapy. Based on the assessment of illness condition and patient physical and psychological status, the Bian-stone therapy was carried out to relieve the clinical symptoms of early-stage acute mastitis, in order to achieve a good prognosis and regain breast-feeding confidence. (本文报告砭石技术干预1例乳痈初起气滞热壅型患者的效果, 梳理砭石技术原理与操作流程。在完善疾病评估、患者身体和心理状况评估的基础上, 通过开展砭石技术, 以期缓解临床症状, 改善预后, 帮助患者重拾母乳喂养信心。)